Genetic instability of the tumor suppressor gene FHIT in normal human cells. Issue 9 (18th June 2013) - Palumbo, Elisa; Tosoni, Elena; Matricardi, Laura; Russo, Antonella
<x xml:space="preserve">Abstract</x> Common fragile sites are hotspots for chromosome instability and co‐localize to cancer genomic rearrangements. Whether these loci may be considered stable in human subjects under physiological conditions remains an open question. Here we show by molecular combing that a small but significant percentage of normal human cells carry an abnormal sequence pattern within the tumor suppressor gene FHIT (3p14.2) at FRA3B. Each sequence variation represents a unique pattern within a normal cell population, and therefore it would remain undetected or not interpreted by genome‐wide analyses. Remarkably, the region is the same as in FHIT rearrangements described in tumors. By analyses on several normal cell lines (proliferating and resting primary lymphocytes, primary fibroblasts, lymphoblastoid cells including clonal cell cultures) we verified that: (a) each cell type displays altered sequence patterns at FHIT; (b) the presence of abnormal sequence patterns is specific for the FHIT locus; and (c) FHIT instability occurs de novo during cell proliferation, and heterogeneous sequence variants progressively accumulate in the cell populations. FHIT has been widely investigated in cancer cells, but to our knowledge this is the first direct evidence of spontaneous and recurrent occurrence of genomic instability at this gene in human subjects, at the same region involved in cancer rearrangements. Our results suggest that common fragile site activity is not restricted to in vitro cell culture and that genomic instability may pre‐exist in normal cells in the absence of exogenous replication stress. © 2013 Wiley Periodicals, Inc.